Pengembangan Media Pembelajaran Berbasis Canva untuk Meningkatkan Minat Belajar Siswa - Rifa Faiz Qoiriina (Prosiding Konferensi Ilmiah Dasar, 2026)
Canva-based learning media is one of the innovations that can support the learning process by presenting instructional materials in a more engaging, interactive, and communicative manner. The various features available in Canva, such as templates, illustrations, icons, images, animations, and videos, enable teachers to develop learning media that are appropriate to the characteristics and learning needs of students. The development of Canva-based learning media involves several stages, including analyzing learning materials, selecting appropriate templates, organizing content using concise and easy-to-understand text, adding relevant visual elements, and finalizing the media in the form of presentation slides or videos. The presentation of learning materials through attractive designs supported by appropriate visual elements can enhance students' attention, motivation, participation, and interest in learning, thereby creating a more effective and enjoyable learning environment. Therefore, Canva can serve as an alternative digital platform that supports teachers in developing creative, innovative, and technology-based learning media.